(untitled) (Hekima Review, 2024)
The invitation to story-telling indicates a significant triadic gain. Firstly, story-telling is revelatory. It discloses the existence of the narrated. This way, the listening audience learns about a world beyond their immediate and enclosed cosmos, a space outside of their familiar space. Secondly, this revelatory sphere creates an enabling environment for epistemic possibilities. Here, story-telling reveals more than mere existence to disclose capabilities. Thirdly, similar to the case of Achebe’s lion, story-telling has a teleological agenda; it is in the telling that glorification becomes a relishable reality. As such, story-telling discloses existence, exposes capabilities and unfolds purpose.